1993
DOI: 10.1007/bf01819137
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of heart rate variability in the sepsis syndrome

Abstract: Sympathetic and parasympathetic activity was evaluated on 39 occasions in 17 patients with the sepsis syndrome, by measurement of the variation in resting heart rate using frequency spectrum analysis. Heart rate was recorded by electrocardiography and respiratory rate by impedance plethysmography. The sepsis syndrome was established on the basis of established clinical and physiological criteria. Subjects were studied, whenever possible, during the period of sepsis and during recovery. Spectral density of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 55 publications
8
62
0
3
Order By: Relevance
“…Considering that murine heart rates range from 400 to 800 beats/min (20), an increase in action potential duration of this magnitude could account for LPS-induced bradycardia (22). Projecting in vitro observations to heart function in situ, these findings account at least in part for reduced heart rate variability (8,30,31,38) and depressed cardiac function that accompanies sepsis (36,44). This may be particularly relevant to neonatal sepsis where mortality is often preceded by reduced heart rate variability and transient decelerations (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that murine heart rates range from 400 to 800 beats/min (20), an increase in action potential duration of this magnitude could account for LPS-induced bradycardia (22). Projecting in vitro observations to heart function in situ, these findings account at least in part for reduced heart rate variability (8,30,31,38) and depressed cardiac function that accompanies sepsis (36,44). This may be particularly relevant to neonatal sepsis where mortality is often preceded by reduced heart rate variability and transient decelerations (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…This is attributable in part to the volume loading that is frequently the initial treatment for septic shock patients to maintain cardiac output and organ perfusion (15, 28). As is often the case in the complexity of sepsis, the prevailing symptoms can mask organ and system failure occurring at a deeper level in the clinical spectrum.The most prevalent sign of myocardial depression in the septic patients, in spite of their increased heart rates, is reduced heart rate variability (HRV), which is prodromal to unfavorable outcome (8,30,31,38). Based on telemetry studies in mice, this reduction in HRV is attributable to lipopolysaccharide (LPS; Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, depletion of neurohypophyseal stores of vasopressin in advanced shock due to excessive baroreceptor firing has been postulated. Second, others 56,57 have postulated autonomic insufficiency, citing lack of baroreflex-mediated bradycardia after vasopressin infusion as evidence. 1 Third, low concentrations of norepinephrine excite central vasopressin- Figure 2.…”
Section: Vasopressin Levels In Shockmentioning
confidence: 99%
“…Landry and coworkers 1 showed that increased metabolism or clearance of vasopressin is not a mechanism of the low vasopressin levels in patients with septic shock. The potential mechanisms of vasopressin deficiency include (1) depletion of pituitary stores of vasopressin after exhaustive release of vasopressin in early septic shock, (2) autonomic dysfunction in patients with septic shock, 56,57 and (3) increased vascular endothelial release of NO within the posterior pituitary, which may downregulate vasopressin production (Table 3). 37 The mechanisms of the exquisite sensitivity of vasodilatory shock patients to vasopressin may also be multifactorial.…”
Section: Mechanisms Of Vasopressin Deficiency In Septic Shock and Sirsmentioning
confidence: 99%